Business Startegy to Adding New Service - Case Study of PT SPARES - Philby, Mohammad; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2019)
Abstract - In a global perspective, every year Airline industries are still growing, aircraft manufacturers deliver more and more aircraft to their customer. From our Directorate General of Civil Aviation (DGCA), until 2015, there were at least 1.448 aircrafts that operate in Indonesia, 121 AOC (Aircraft Operation Certificate) Holder that consisting of scheduled airlines, scheduled cargo airlines, un-scheduled airlines, un-scheduled cargo airlines, and non-profit airlines. There are also 33 MRO (maintenance repair organization) that support all aircraft that not only operate here but also from overseas market. PT SPARES was founded in October 2014 with the main objective is to provide drone inspection service and consumable spare part for aviation industries in Indonesia but now its main selling point is aircraft consumable spare part services for airlines. The Objective of this thesis is to analyse the possibility of PT SPARES to expand their business in order to survive and to provide a recommendation regarding the new Business Model if expansion is feasible. Researcher is proposing to open logistics service to the customer with utilizing the third-party logistics model to minimized the investment. In PT SPARES, there is 7 key challenge parameter that can affect PT SPARES for expanding their line of business. The 7 key parameter are Government Policy on Export & Import Industry – Economic Policy Package VIII, Government Policy in Aviation Industry – Deregulation of Airline Tariff, Aviation Condition – Growth of Aircraft in Indonesia, Logistic Transport Condition – Interconnecting and creating new connection between cities, Skilled employee – There is needed a new skilled employee in the aviation & logistics, Market Share – Take on niche market and a need of Government support in Export & Import – Improvement of Export & Import system. Based on these findings, we found that they need to prepare how to handle related challenges in order to survive in logistics industries and proposed new Business Canvas Model with the new value proposition, Good government connection, Efficient customs brokerage, Efficient logistics service, and One-stop spare-parts solution. With the new value proposition, the operation of the PT SPARES will be change to accommodate it. There are also several implementations plans that we propose, in short-term, medium-term and long-term plan that hopefully can be a guidance for PT SPARES to achieve the sustainability and maintain and deliver customer expectation and satisfactory.Keywords: Airline, Aviation, Logistics, Spare Parts, Business Strategy, Value Preposition, Risk Management, Sustainability.